Preparation and application of a tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite electrode
Patent Information
- Application Number
- CN202611106381.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明旨在解决现有LD电化学检测过程中存在的选择性不足、灵敏度低以及检测限较高等问题,提供一种酪氨酸酶修饰分子印迹PEDOT/CuCo@氮掺杂碳纳米片阵列/三维石墨烯复合材料电极及其制备方法
1.本发明采用一步水热法结合高温热解方法制备CuCo@氮掺杂碳纳米片阵列/三维石墨烯复合材料,利用三维石墨烯优异的导电网络和CuCo双金属纳米颗粒的协同催化作用,提高了电极材料的电子传输能力和电催化活性;同时,氮掺杂碳纳米片阵列结构增加了电极表面的活性位点数量,有利于LD分子的快速吸附和界面电子转移。
Smart Images

Figure CN122983157A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterial preparation and electrochemical biosensor detection technology, and relates to a method for preparing a tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode and its application in the electrochemical detection of levodopa. Background Technology
[0002] Parkinson's disease (PD) is the second most common neurodegenerative disease worldwide. Treatment primarily relies on levodopa crossing the blood-brain barrier to replenish depleted dopamine levels. However, a key challenge in PD treatment is the accurate detection of levodopa (LD) concentrations. Too low an LD concentration may lead to treatment failure, while too high a concentration may damage the nervous system, ultimately exacerbating PD symptoms. Therefore, a reliable, accurate, and rapid method for monitoring LD concentrations is urgently needed. Electrochemical detection technology, with its advantages of fast detection speed, high sensitivity, and ease of operation, has rapidly developed and been widely applied. Among these advancements, developing novel electrode materials with high catalytic activity, high conductivity, and excellent interfacial mass transfer capabilities is a crucial approach to improving electrochemical detection performance.
[0003] In recent years, metal / carbon composites derived from metal-organic frameworks (MOFs) have attracted much attention in the field of electrochemical sensing due to their advantages such as low preparation cost, preservation of precursor morphology, high catalytic activity, and good conductivity. Bimetallic nanoparticle / carbon materials derived from MOFs can provide higher metal loading and abundant active sites. Among them, CuCo nanoparticles loaded with carbon, formed by the pyrolysis of CuCo-MOFs, exhibit excellent electrocatalytic activity and conductivity, and are expected to be applied to electrochemical detection in LDs. Furthermore, the nanosheet array (NSA) morphology exposes more accessible active sites and promotes electrolyte penetration and rapid molecular diffusion, thereby significantly improving mass transfer efficiency. Using highly conductive three-dimensional graphene foam as a framework, CuCo@nitrogen-doped carbon nanosheet arrays can be generated in situ on its surface through high-temperature pyrolysis, forming a continuous conductive network. This structure is beneficial for the adsorption of high surface energy Cu and Co nanoparticles onto LDs and promotes efficient charge transport.
[0004] Molecular imprinting technology can construct specific recognition cavities in polymer layers that are highly matched to template molecules in terms of size, shape, and functional group distribution, thereby endowing electrochemical sensors with excellent selectivity. Poly(3,4-ethylenedioxythiophene) (PEDOT) has excellent conductivity, electrochemical stability, and good film-forming properties, and is widely used to construct molecularly imprinted polymer sensing interfaces. By electropolymerizing a molecularly imprinted PEDOT layer on the surface of CuCo@nitrogen-doped carbon nanosheet array / 3D graphene, a specific recognition layer with high selectivity for LD can be formed, thus establishing a signal response pathway based on a molecularly imprinted recognition mechanism. In addition, tyrosinase exhibits excellent specificity and catalytic activity for LD. Immobilizing tyrosinase on the surface of molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene can achieve efficient enzymatic catalytic signal amplification for LD, thereby constructing a second signal response pathway based on enzymatic catalysis. Therefore, the synergistic integration of molecularly imprinted recognition and enzymatic catalysis holds promise for achieving highly sensitive and selective dual-channel electrochemical detection of LD. In summary, this invention provides a method for preparing a tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode, and applies it to the electrochemical detection of an LD. Summary of the Invention
[0005] This invention aims to address the problems of insufficient selectivity, low sensitivity, and high detection limit in existing LD electrochemical detection processes, and provides a tyrosinase-modified molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode and its preparation method.
[0006] I. Preparation of CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material Weigh out 0.02-0.4 mM copper nitrate, 0.02-0.4 mM nickel nitrate and 0.01-0.8 mM dimethylimidazole and add them to 20-80 mL of deionized water. Immerse the three-dimensional graphene oxidized by concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) into the above precursor solution and stir at 25-100°C for 4-16 h. After the reaction is completed, wash with deionized water and ethanol solution 3 times each. After freeze-drying, calcine at 500-900°C for 3 h under argon protection atmosphere to obtain CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material. II. Fabrication of Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode The CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material obtained in step one was loaded onto ITO conductive glass as the working electrode. Platinum wire and silver / silver chloride were used as the counter electrode and reference electrode, respectively. L-DOPA and 3,4-ethylenedioxythiophene (EDOT) were added to 10-40 mL of PBS buffer solution at a molar ratio of 1:1 to 1:5. The mixture was stirred at room temperature for 1-3 h. Cyclic voltammetry was used to scan the potential range of -0.2 to 0.8 V at a scan rate of 5-200 mV / s for 10-100 cycles to electropolymerize a molecularly imprinted PEDOT film on the surface of the working electrode, thus obtaining the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material electrode. III. Fabrication of Tyrosinase-Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode Using the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode obtained in step two as a substrate, 4~16 μL of tyrosinase solution was added dropwise, and cross-linking and fixation were performed using 0.25~2.5% glutaraldehyde (GLU). The reaction was carried out at 4℃ or room temperature for 0.5~12 h. After the reaction, the electrode surface was washed with PBS buffer solution and naturally dried to obtain the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode.
[0007] Compared with existing technologies, the present invention has the following advantages: 1. This invention employs a one-step hydrothermal method combined with a high-temperature pyrolysis method to prepare CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material. By utilizing the excellent conductive network of three-dimensional graphene and the synergistic catalytic effect of CuCo bimetallic nanoparticles, the electron transport capability and electrocatalytic activity of the electrode material are improved. At the same time, the nitrogen-doped carbon nanosheet array structure increases the number of active sites on the electrode surface, which is beneficial to the rapid adsorption of LD molecules and interfacial electron transfer.
[0008] 2. This invention constructs a molecularly imprinted PEDOT recognition layer on the surface of CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material by electropolymerization. By utilizing the matching effect between the molecularly imprinted cavity and the LD in terms of spatial structure and functional group distribution, the specific recognition of the LD is achieved, effectively reducing the interference of coexisting substances in complex samples on the detection results and improving the detection selectivity.
[0009] 3. In this invention, tyrosinase is further immobilized on the surface of a molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode. By utilizing the specific catalytic effect of tyrosinase on the LD, the detection signal is further amplified, thereby achieving high selectivity and high sensitivity detection of the LD. It has a good linear response in the concentration range of 0~60 μM, a sensitivity of 5.37 μA·μM⁻¹·cm⁻², and a detection limit as low as 0.016 μM. Attached Figure Description
[0010] Figure 1 Morphological characterization of the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material; Figure 2 Characterization of the structure, chemical bonding, valence state, and surface composition of the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material; Figure 3 Electrochemical behavior of different electrodes; Figure 4 A schematic diagram of the DPV response and sensing mechanism of a tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode for LD detection; Figure 5 Performance of tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite electrode for LD detection in whole blood samples; Detailed Implementation
[0011] Specific Implementation Method 1: A method for preparing a tyrosinase-modified molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode, comprising the following steps: I. Preparation of CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material Weigh out 0.02-0.4 mM copper nitrate, 0.02-0.4 mM nickel nitrate and 0.01-0.8 mM dimethylimidazole and add them to 20-80 mL of deionized water. Immerse the three-dimensional graphene oxidized by concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) into the above precursor solution and stir at 25-100°C for 4-16 h. After the reaction is completed, wash with deionized water and ethanol solution 3 times each. After freeze-drying, calcine at 500-900°C for 3 h under argon protection atmosphere to obtain CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material. II. Fabrication of Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode The CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material obtained in step one was loaded onto ITO conductive glass as the working electrode. Platinum wire and silver / silver chloride were used as the counter electrode and reference electrode, respectively. L-DOPA and 3,4-ethylenedioxythiophene (EDOT) were added to 10-40 mL of PBS buffer solution at a molar ratio of 1:1 to 1:5. The mixture was stirred at room temperature for 1-3 h. Cyclic voltammetry was used to scan the potential range of -0.2 to 0.8 V at a scan rate of 5-200 mV / s for 10-100 cycles to electropolymerize a molecularly imprinted PEDOT film on the surface of the working electrode, thus obtaining the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material electrode. III. Fabrication of Tyrosinase-Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode Using the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode obtained in step two as a substrate, 4~16 μL of tyrosinase solution was added dropwise, and cross-linking and fixation were performed using 0.25~2.5% glutaraldehyde (GLU). The reaction was carried out at 4℃ or room temperature for 0.5~12 h. After the reaction, the electrode surface was washed with PBS buffer solution and naturally dried to obtain the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode.
[0012] Specific Implementation Method Two: A method for preparing a tyrosinase-modified molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode, comprising the following steps: The difference between this embodiment and embodiment one is that in step one, the CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material is obtained by calcination at 500~700℃ for 3 h under an argon protective atmosphere. Otherwise, it is the same as embodiment one. Specific Implementation Method 3: A method for preparing a tyrosinase-modified molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode, comprising the following steps: The difference between this embodiment and Embodiment 1 and Embodiment 2 is that in step 2, levodopa and 3,4-ethylenedioxythiophene (EDOT) are added to 15-30 mL of PBS solution at a molar ratio of 1:3 to 1:5, stirred for 1-3 hours, and cyclic voltammetry is used in the range of -0.2-0.6V at a scan rate of 30-60 mV / s for 10-60 cycles. The rest is the same as in Embodiment 1 to Embodiment 2. The effectiveness of the present invention was verified by the following experiments: This experiment presents a method for preparing a tyrosinase-modified molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode, comprising the following steps: I. Preparation of CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material 0.2 mM copper nitrate, 0.2 mM nickel nitrate and 0.4 mM dimethylimidazole were weighed and added to 80 mL of deionized water. The three-dimensional graphene oxidized by concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) was immersed in the above precursor solution and stirred at 25°C for 8 h. After the reaction was completed, it was washed 3 times each with deionized water and ethanol solution. After freeze-drying, it was calcined at 600°C for 3 h under argon protection to obtain CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material. II. Fabrication of Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode The CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material obtained in step one was loaded onto ITO conductive glass as the working electrode. Platinum wire and silver / silver chloride were used as the counter electrode and reference electrode, respectively. L-DOPA and 3,4-ethylenedioxythiophene (EDOT) were added to 20 mL of PBS buffer solution at a molar ratio of 1:4. The mixture was stirred at room temperature for 1 h. Cyclic voltammetry was used to scan the potential range of -0.2 to 0.6 V for 45 cycles at a scan rate of 50 mV / s to electropolymerize on the surface of the working electrode to form a molecularly imprinted PEDOT film, thus obtaining the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite electrode. III. Fabrication of Tyrosinase-Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode Using the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite electrode obtained in step two as a substrate, 12 μL of tyrosinase solution was added dropwise, and cross-linking and fixation were performed using 1% glutaraldehyde (GLU). The reaction was carried out at 4℃ or room temperature for 0.5 h. After the reaction, the electrode surface was washed with PBS buffer solution and allowed to dry naturally to obtain the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite electrode.
[0013] This invention uses a three-electrode testing system to study the electrochemical properties of materials. The three electrodes consist of a platinum wire as the counter electrode, a silver / silver chloride electrode as the reference electrode, and a 0.1 M PBS solution as the electrolyte.
[0014] Figure 1The morphology of a tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material (TYR / MI-PEDOT / CuCo@NCNSA / 3D GF) is shown. The CuCo-MOF nanosheet array (CuCo-MOF NSA) prepared by a one-step hydrothermal method is uniformly grown on the surface of 3D graphene (3D GF), forming a regular triangular nanosheet array structure. Figure 1 ab). After high-temperature pyrolysis, the obtained CuCo@NCNSA / 3D GF still maintains the complete nanosheet array morphology, and the interlayer porosity is significantly increased ( Figure 1 cd). After electropolymerization to form a MI-PEDOT layer and immobilizing TYR on the CuCo@NCNSA / 3D GF surface, the resulting TYR / MI-PEDOT / CuCo@NCNSA / 3D GF still maintains the original nanosheet array structure, but the surface roughness is significantly increased. Figure 1 TEM images of CuCo@NCNSA / 3D GF after ultrasonic dispersion show that a large number of nanoparticles are uniformly distributed on the surface of the nanosheets. Figure 1 HRTEM images show that the nanoparticles have lattice fringe spacings of 0.209 nm and 0.206 nm, corresponding to the (111) crystal planes of face-centered cubic Cu and Co, respectively. Figure 1 Hi). Three clear diffraction rings appeared in the SAED pattern, corresponding to the (111) crystal plane of Cu and the (111) and (200) crystal planes of Co, respectively, confirming the formation of CuCo bimetallic nanoparticles. At the same time, no obvious carbon material diffraction rings were observed, indicating that the nitrogen-doped carbon nanosheets (NC) derived from CuCo-MOFs during pyrolysis mainly exhibit an amorphous structure. Figure 1 j). EDS elemental distribution results of CuCo@NCNSA show that C, Co, Cu, and N elements are uniformly distributed in the nanosheet structure. Figure 1 ko).
[0015] Figure 2 The crystal structure, chemical bonding, and elemental valence states of TYR / MI-PEDOT / CuCo@NCNSA / 3D GF are shown. XRD patterns are also presented. Figure 2In a), the characteristic diffraction peaks of the precursor CuCo-MOFs NSA in the 0~20° range basically disappeared after high-temperature pyrolysis, indicating that its original crystal structure had changed. At the same time, new diffraction peaks appeared at 2θ=43.1°, 44.3°, 49.8° and 51.6°, corresponding to the (111) and (200) crystal planes of metallic Cu and metallic Co, respectively, indicating that Cu and Co ions were successfully reduced to the metallic state during pyrolysis. In addition, the diffraction peak intensities at 26.6° and 45.1° corresponding to the (002) and (111) crystal planes of graphitic carbon were significantly enhanced, indicating that a conductive carbon framework composed of NCNSA and 3D GF was formed during pyrolysis. Figure 2 b shows the Raman spectrum of CuCo@NCNSA / 3D GF. D-bands, G-bands, and 2D bands appear at 1351, 1592, and 3036 cm⁻¹, respectively. The D-band corresponds to defects and disordered structures in carbon materials, and the G-band corresponds to sp... 2 The in-plane vibrations of hybrid carbon atoms and the 2D bands reflect the layered structure of graphite. The IG / ID value of this material is 0.93, indicating a high density of defect sites in the carbon framework; at the same time, the broad and gentle 2D bands indicate that the obtained carbon material is mainly composed of a multilayered graphite structure.
[0016] XPS Full Spectrum ( Figure 2 c) shows that CuCo@NCNSA / 3D GF is mainly composed of C, N, Co, Cu, and N elements. High-resolution C1s spectra ( Figure 2 d) can be decomposed into four peaks at 284.8, 285.4, 286.6, and 288.1 eV, corresponding to C, CN, CO, and C=O bonds, respectively. The presence of CN bonds indicates that nitrogen atoms have been successfully doped into the carbon framework. N 1s spectrum ( Figure 2 In (e), the peaks at 399.1 and 401.1 eV are attributed to pyrrole nitrogen and graphitic nitrogen, respectively, further confirming the formation of nitrogen-doped carbon materials. High-resolution Co 2p spectra ( Figure 2 f) shows that the peaks at 778.7 and 793.8 eV correspond to metallic Co. 0 Furthermore, since Co nanoparticles are prone to surface oxidation upon exposure to air, Co was observed at 781.1, 782.8, 796.4, and 797.4 eV, respectively. 3+ and Co 2+ The corresponding characteristic peaks, accompanied by satellite peaks at 786.8 and 802.8 eV, indicate the presence of a small amount of oxidized Co species on the material surface. High-resolution Cu2p spectrum ( Figure 2 In g), the peaks at 932.9 and 952.9 eV correspond to Cu 2p, respectively. 3 / 2 and Cu 2p 1 / 2 Mainly derived from Cu0 and Cu + Species. FT-IR spectroscopy ( Figure 2 (hi) shows that both CuCo@NCNSA / 3D GF and TYR / MI-PEDOT / CuCo@NCNSA / 3D GF have a maximum thickness of 3430 cm⁻¹. -1 A broad absorption peak appears at 1083 cm⁻¹, corresponding to the OH stretching vibration. Characteristic peaks at 1083, 987, and 859 cm⁻¹ are attributed to the COC and CSC vibrations in PEDOT, respectively, while the absorption peak at 542 cm⁻¹ corresponds to the stretching vibration of the metal-oxygen (MO) bond. After TYR fixation, the amide I band absorption peak near 1640 cm⁻¹ is significantly enhanced, indicating that TYR has been successfully fixed on the MI-PEDOT / CuCo@NCNSA / 3D GF surface. Figure 2 i). The above analytical results collectively confirm the successful construction of the TYR / MI-PEDOT / CuCo@NCNSA / 3D GF composite electrode.
[0017] Figure 3 The electrochemical performance and optimization results of different modified electrodes are presented. The CV curves ( Figure 3 In (a), the CuCo@NCNSA / 3D GF electrode exhibited the smallest CV curve area and a lower redox peak current, indicating relatively low electrochemical activity. After the electropolymerization of the CuCo@NCNSA / 3D GF surface to form a MI-PEDOT layer, the CV curve area and redox peak current of the electrode showed a trend of first increasing and then decreasing with the increase of the LD to EDOT molar ratio. When the LD to EDOT molar ratio was 1:4, the MI-PEDOT / CuCo@NCNSA / 3D GF electrode exhibited the largest CV curve area and a higher redox peak current, indicating that this ratio is conducive to the formation of an appropriate number of molecularly imprinted recognition sites and maintaining good electron transport capability. After further immobilization of TYR, the TYR / MI-PEDOT / CuCo@NCNSA / 3D GF electrode showed the largest CV curve area and the highest redox peak current, indicating that tyrosinase modification further enhanced the electrochemical response of the electrode. The effects of TYR loading and GLU mass fraction on the electrochemical performance of the MI-PEDOT / CuCo@NCNSA / 3D GF electrode were further investigated using EIS. Figure 3 bc). When TYR solution (5 mg·mL) -1 When the fixed amount is from 4 to 16 μL, the semi-circular diameter in the high-frequency region gradually increases, that is, the charge transfer resistance (Rct) increases from 8.6 Ω to 10.1 Ω. Figure 3(b) This indicates that increasing the TYR loading will, to some extent, hinder interfacial electron transport. Under the optimal fixed TYR amount (12 μL), the effect of GLU mass fraction was further investigated. As the GLU mass fraction increased from 0.25% to 2.5%, Rct increased from 9.5 Ω to 12.4 Ω ( Figure 3 c) indicates that an excessively high GLU mass fraction will increase the resistance to interfacial electron transport. Figure 3 d represents the equivalent circuit model used in EIS fitting, including solution resistance (Rs), constant phase angle element (CPE), charge transfer resistance (Rct), and Warburg impedance (W). Under optimized conditions (12 μL TYR, 0.5% GLU mass fraction), the electrode's Rct is only 10.2 Ω. The electrolyte pH has a significant impact on the electrochemical oxidation behavior of the LD. Figure 3 e). As pH increases, the oxidation peak potential gradually shifts towards the negative direction, while the oxidation peak current shows a trend of first increasing and then decreasing, reaching its maximum at pH=7, indicating that neutral conditions are more favorable for the electrocatalytic oxidation of LD. The effect of temperature on electrode catalytic performance was evaluated using UV-Vis. Figure 3 f), the results showed that the absorbance at 475 nm decreased only slightly within the temperature range of 15–65 °C, indicating that the electrode maintained good catalytic activity over a wide temperature range; however, the absorbance decreased significantly above 55 °C, indicating that high temperature led to a decrease in TYR catalytic activity. Therefore, considering both detection performance and experimental conditions, subsequent experiments were conducted at room temperature (25 °C). Furthermore, the effect of the scan rate on the electrochemical behavior of the electrode was investigated ( Figure 3 g). When the scan rate increased from 15 to 50 mV·s⁻¹, the redox peak current gradually increased, and the oxidation peak current showed a good linear relationship with the square root of the scan rate (g). Figure 3 h), its linear regression equation is: Ipa=(0.088±0.002)-(0.194±0.013)v 1 / 2 (R) 2 =0.9971), indicating that the electrochemical oxidation process of LD on the TYR / MI-PEDOT / CuCo@NCNSA / 3D GF electrode is mainly diffusion-controlled.
[0018] The electrochemical detection performance of different modified electrodes in the concentration range of 0–60 μM LD was studied using density functional theory (DFT), and the recognition mechanism of LD was further analyzed by combining density functional theory (DFT) calculations. Figure 4 For the TYR / MI-PEDOT / CuCo@NCNSA / 3D GF electrode, the oxidation peak current gradually increases with increasing LD concentration. Figure 4a) The oxidation peak current and LD concentration show a good linear relationship, and the linear fitting equation is: ILD = (5.984 ± 0.995) + (2.059 ± 0.048)CLD (R² = 0.9978) Figure 4 b). Under optimized conditions, the TYR / MI-PEDOT / CuCo@NCNSA / 3D GF electrode exhibited the highest detection sensitivity, reaching 5.37 μA·μM⁻¹·cm⁻². To further elucidate the sensing mechanism of this electrode for LD, a schematic diagram of the LD detection mechanism based on the synergistic effect of the dual channels was constructed ( Figure 4 c). TYR, immobilized on the surface of the MI-PEDOT layer, serves as a catalytic channel, catalyzing the oxidation of LD to dopaquinone, promoting electron generation, and achieving rapid electron transport through a highly conductive network constructed from MI-PEDOT and CuCo@NCNSA / 3D GF, thereby enhancing the electrochemical response signal. Simultaneously, the MI-PEDOT layer acts as a molecular recognition channel; the molecularly imprinted cavity formed within it can achieve specific recognition of LD through spatial matching and functional group interactions, improving the sensor's selectivity. To further reveal the interaction between LD and the electrode interface, DFT calculations were used to construct adsorption models of LD on the MI-PEDOT / Cu(111) and MI-PEDOT / Co(111) surfaces. The calculation results show that the adsorption energies of LD on the MI-PEDOT / Cu(111) and MI-PEDOT / Co(111) surfaces are -5.59 eV and -7.49 eV, respectively, indicating that LD can form stable adsorption at the composite interface. Figure 4 After LD adsorption, both the MI-PEDOT / Cu(111) and MI-PEDOT / Co(111) models showed significant charge redistribution, forming electron-rich regions (red) and electron-depleted regions (blue), and electrons transferred from LD to the MI-PEDOT / Cu and MI-PEDOT / Co interfaces. Figure 4 The above results indicate that the MI-PEDOT / CuCo@NCNSA interface can promote the stable adsorption of LD molecules and interfacial electron transport. In summary, the efficient enzymatic catalysis of TYR combined with the specific molecular recognition ability of MI-PEDOT forms a synergistically enhanced dual-channel detection mechanism, achieving high sensitivity and high selectivity for LD detection.
[0019] To verify the self-filtration capability of polyacrylamide (PAM-H) hydrogel for blood samples, blood was first added to a glass vial containing PAM-H for observation. During the 1-60 min test, no blood penetration into the PAM-H structure was observed. Further, methylene blue (MB) stained blood was added to the PAM-H surface, revealing a distinct blue hue inside the PAM-H, while large molecules in the blood did not significantly permeate. This indicates that large molecules such as blood cells, fibrinogen, and lipids can be effectively retained by PAM-H, while small aqueous components containing MB can pass through the PAM-H structure. Figure 5 a). Subsequently, the TYR / MI-PEDOT / CuCo@NCNSA / 3D GF electrode was combined with a portable electrochemical sensor and further integrated with PAM-H hydrogel to evaluate its detection stability in complex blood environments. The current response of the unmodified PAM-H electrode decreased significantly after contact with blood, while the current signal of the electrode with PAM-H remained basically stable. Figure 5 b). The results showed that PAM-H can effectively block direct contact between macromolecular components in blood and the electrode interface, reducing the impact of biocontamination on electrode performance and enabling the electrode to maintain a stable electrochemical response in a blood environment. Further evaluation was conducted using IT to assess the electrode's ability to perform point-of-care testing (POCT) of LD in a blood environment. Within the 0–20 μM LD concentration range, the current response gradually increased with increasing LD concentration. Figure 5 c). A good linear relationship exists between LD concentration and current response; the linear fitting equation is: I LD =(43.984±10.862)+(12.051±1.946)C LD (R²=0.9055) Figure 5 d). The above results indicate that the TYR / MI-PEDOT / CuCo@NCNSA / 3D GF electrode with PAM-H self-filtration function can effectively reduce blood matrix interference and achieve rapid quantitative detection of LD in the blood environment.
Claims
1. The preparation and application of a tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode, characterized in that... The preparation method of this composite material electrode is carried out according to the following steps: I. Preparation of CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material Weigh out 0.02-0.4 mM copper nitrate, 0.02-0.4 mM nickel nitrate and 0.01-0.8 mM dimethylimidazole and add them to 20-80 mL of deionized water. Immerse the three-dimensional graphene oxidized by concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) into the above precursor solution and stir at 25-100°C for 4-16 h. After the reaction is completed, wash with deionized water and ethanol solution 3 times each. After freeze-drying, calcine at 500-900°C for 3 h under argon protection atmosphere to obtain CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material. II. Fabrication of Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode The CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material obtained in step one was loaded onto ITO conductive glass as the working electrode. Platinum wire and silver / silver chloride were used as the counter electrode and reference electrode, respectively. L-DOPA and 3,4-ethylenedioxythiophene (EDOT) were added to 10-40 mL of PBS buffer solution at a molar ratio of 1:1 to 1:
5. The mixture was stirred at room temperature for 1-3 h. Cyclic voltammetry was used to scan the potential range of -0.2 to 0.8 V at a scan rate of 5-200 mV / s for 10-100 cycles to electropolymerize a molecularly imprinted PEDOT film on the surface of the working electrode, thus obtaining the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / 3D graphene composite material electrode. III. Fabrication of Tyrosinase-Molecularly Imprinted PEDOT / CuCo@Nitrogen-Doped Carbon Nanosheet Array / Three-Dimensional Graphene Composite Electrode Using the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode obtained in step two as a substrate, 4~16 μL of tyrosinase solution was added dropwise, and cross-linking and fixation were performed using 0.25~2.5% glutaraldehyde (GLU). The reaction was carried out at 4℃ or room temperature for 0.5~12 h. After the reaction, the electrode surface was washed with PBS buffer solution and naturally dried to obtain the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode.
2. The method for preparing the CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite material according to claim 1, characterized in that, Weigh out 0.1-0.4 mM copper nitrate, 0.1-0.4 mM nickel nitrate and 0.1-0.6 mM dimethylimidazole and add them to 20-80 mL of deionized water. Immerse the three-dimensional graphene oxidized by concentrated nitric acid and concentrated sulfuric acid (volume ratio 3:1) into the above precursor solution and stir at 25-100°C for 4-16 h.
3. The method for preparing the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode according to claim 1, characterized in that, In step two, levodopa and 3,4-ethylenedioxythiophene (EDOT) in a molar ratio of 1:2 to 1:4 were added to 10 to 30 mL of PBS buffer solution and stirred at room temperature for 1 to 3 h. Cyclic voltammetry was then used to scan the potential range of -0.2 to 0.6 V at a scan rate of 10 to 100 mV / s for 15 to 80 cycles.
4. The method for preparing the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode according to claim 1, characterized in that... In step three, glutaraldehyde (GLU) with a mass fraction of 0.25~1% is used as a crosslinking agent to immobilize 8~16 μL of tyrosinase on the surface of the molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode to form a tyrosinase modified layer.
5. The application of the tyrosinase-molecularly imprinted PEDOT / CuCo@nitrogen-doped carbon nanosheet array / three-dimensional graphene composite electrode prepared according to any one of claims 1 to 4 in the electrochemical detection of levodopa.